J'ai toujours voulu être une sainte - Mersch, Geneviève; Barde, Séverine; Kremer, Marie; Lefevre, Thierry; Godinas, Jeanine
Compelling Belgian coming-of-age drama about a teen girl (astonishing Marie Kremer) dealing with long-buried momma-abandonment issues. Some cans of worms are best left unopened, and director Geneviève Mersch (in her feature debut) brings us a wonderful little story about a good person who goes a bit mad. [www.threeimaginarygirls.com]